Review paperTotal skin electron irradiation techniques: a review - Piotrowski, Tomasz; Milecki, Piotr; Skórska, Małgorzata; Fundowicz, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Total skin electron irradiation (TSEI) has been employed as one of the methods of mycosis fungoides treatment since the mid-twentieth century. In order to improve the effects and limit the complications following radiotherapy, a number of varieties of the TSEI method, frequently differing in the implementation mode have been developed. The paper provides a systematic review of the different varieties of TSEI. The discussed differences concerned especially: (i) technological requirements and geometric conditions, (ii) the alignment of the patient, (iii) the number of treatment fields, and (iv) dose fractionation scheme.